Penerapan Inkuiri pada Mata Palajaran Fiqh di MTsN Kuta Baro Aceh Besar - Nurmalawati Nurmalawati; Mustabsyirah M. Husein; Ainal Mardhiah (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2016)
Apply the learning that focuses on skills in problem solving, observing the object, take decisions, able to think logically, systematically and asking questions is a form of inquiry that the application process should be applied on the subjects of Fiqh in MTsN Kuta Baro, Aceh Besar. This study is intended to answer the question of how the learning process with the adoption of Inquiry on the subjects of Fiqh in Kuta Baro, Aceh Besar MTsN material understanding of Islamic law on food and beverages. Observations indicate that the teacher is less effective to apply the learning process and less than the maximum learning methods, so that the students look no influence on learning outcomes. The purpose of this study to know the learning process with the implementation of inquiry on the subject matter Fiqh Understanding Islamic law on food and beverages. This study uses classroom action research, in this study the authors using observation, testing and documentation to collect data. This classroom action research conducted in MTsN Kuta Baro, Aceh Besar on the subjects of Fiqh. As the subjects in this study were students of class VIII. The research was conducted in the 2nd half (two) in the academic year 2014/2015. All data collected through the research, the authors if by counting the frequency and percentage of all alternative answers to each question. Results showed that the adoption of Inquiry on materials Understanding Islamic law on food and beverages in Fiqh lessons can create teaching and learning process more interesting and help improve students' skills in lessons Fiqh.